Предмет: Математика,
автор: robutana3
2*(2x-1)-3*(x-2)=6+4*(3-2x)
Ответы
Автор ответа:
1
Ответ:
Пошаговое объяснение:
2*(2x-1)-3*(x-2)=6+4*(3-2x)
4x - 2 - 3x + 6 = 6 + 12 - 8x
x + 4 = 18 - 8x
x + 8x = 18 - 4
9x = 14
x = 14 : 9
x = 1 5/9
Автор ответа:
1
Ответ
2(2x-1)-3(x-2)=6+4(3-2x)
4x-2-3x+6=6+12-8x
4x-3x+8x=6+12+2-6
9x=14
x=14/9
x=1 5/9
Пошаговое объяснение:
Похожие вопросы
Предмет: Русский язык,
автор: BucKaC
Предмет: Русский язык,
автор: lobovaliliya
Предмет: Русский язык,
автор: ирина270
Предмет: Литература,
автор: viktoriaglazik
Предмет: История,
автор: Vasena27